Intravenous cangrelor use for neuroendovascular procedures: a two-center experience and updated systematic review - Desai, Harsh; Al-Salihi, Mohammed Maan; Morsi, Rami Z.; Vayani, Omar R.; Kothari, Sachin A.; Thind, Sonam; Carrión-Penagos, Julián; Baskaran, Archit; Tarabichi, Ammar; Bonderski, Veronica A.; Siegler, James E.; Hahn, Mary; et al. (Frontiers in Neurology, 2023)
Background The optimal antiplatelet therapy regimen for certain neuroendovascular procedures remains unclear. This study investigates the safety and feasibility of intravenous dose-adjusted cangrelor in patients undergoing acute neuroendovascular interventions. Methods We conducted a retrospective chart review of all consecutive patients on intravenous cangrelor for neuroendovascular procedures between September 1, 2020, and March 13, 2022. We also conducted an updated systematic review and meta-analysis using PubMed, Scopus, Web of Science, Embase and the Cochrane Library up to February 22, 2023. Results In our cohort, a total of 76 patients were included [mean age (years): 57.2 ± 18.2, males: 39 (51.3), Black: 49 (64.5)]. Cangrelor was most used for embolization and intracranial stent placement (n = 24, 32%). Approximately 44% of our patients had a favorable outcome with a modified Rankin Scale (mRS) score of 0 to 2 at 90 days (n = 25/57); within 1 year, 8% of patients had recurrent or new strokes (n = 5/59), 6% had symptomatic intracranial hemorrhage [sICH] (4/64), 3% had major extracranial bleeding events (2/64), and 3% had a gastrointestinal bleed (2/64). In our meta-analysis, 11 studies with 298 patients were included. The pooled proportion of sICH and intraprocedural thromboembolic complication events were 0.07 [95% CI 0.04 to 1.13] and 0.08 [95% CI 0.05 to 0.15], respectively. Conclusion Our study found that intravenous cangrelor appears to be safe and effective in neuroendovascular procedures, with low rates of bleeding and ischemic events. However, further research is needed to compare different dosing and titration protocols of cangrelor and other intravenous agents.